Bioaerosol Detection Technologies - Jonsson, Per; Olofsson, Göran; Tjärnhage, Torbjörn (Integrated Analytical Systems, 2014)
This book is intended to give technological background and practical examples, but also to give general insight into the on-going technology development in the area of biodetection. The content is therefore suitable for an array of stakeholders (decision makers, purchasing officers, etc.) and end-users of biodetection equipment within the areas of health, environment, safety and security, and military preparation. The book is divided into three sections. The first section discusses the fundamental physical and biological properties of bioaerosol's. The second section goes into more detail and discusses in-depth the most commonly used detection principles. The third section of the book is devoted to technologies that have been used in standoff applications. The last section of the book gives an overview of trends in bioaerosol detection. The reader of this book will gain knowledge about the different biodetection technologies and thus better judge their capabilities in relation to desired applications.